Upaya Pendekatan Kedokteran Keluarga pada Perempuan Usia 52 Tahun dengan DM Tipe 2 di Kecamatan Nisam Kabupaten Aceh Utara - Muhammad Syifa Albi Nasution; Noviana Zara (Inovasi Kesehatan Global, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder whose prevalence continues to rise, making it a major challenge for health systems worldwide. This disease results from a combination of insulin resistance and impaired pancreatic β-cell function, leading to persistent hyperglycemia and increased risk of long-term complications affecting the kidneys, cardiovascular system, nervous system, and eyes. This report describes the case of a 52-year-old woman diagnosed with T2DM for approximately ten years. The patient presented with fatigue, nocturnal polyuria, nausea after meals, significant weight loss, and tingling in her extremities. Laboratory findings revealed an HbA1c level of 12%, reflecting very poor glycemic control. A family medicine approach was applied through detailed history taking, physical and laboratory examinations, home visits, and completion of a family folder to assess clinical, personal, social, and functional aspects. Interventions included counseling on balanced diet, encouragement of regular physical activity, education on diabetic foot care, and pharmacological treatment with metformin and insulin. The family received counseling about hereditary risk factors, the importance of emotional support, and the need for consistent monitoring of health status. The patient was still capable of light daily activities, supported by a highly functional family environment with an APGAR score of 10. A holistic family medicine–based approach was shown to improve treatment adherence, patient knowledge, and overall quality of life. Therefore, management of T2DM requires a comprehensive strategy that integrates promotive, preventive, curative, and rehabilitative components, emphasizing the active involvement of family and community at the primary care level to reduce complications, slow disease progression, and enhance patient well-being. Keywords: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder whose prevalence continues to rise, making it a major challenge for health systems worldwide. This disease results from a combination of insulin resistance and impaired pancreatic β-cell function, leading to persistent hyperglycemia and increased risk of long-term complications affecting the kidneys, cardiovascular system, nervous system, and eyes. This report describes the case of a 52-year-old woman diagnosed with T2DM for approximately ten years. The patient presented with fatigue, nocturnal polyuria, nausea after meals, significant weight loss, and tingling in her extremities. Laboratory findings revealed an HbA1c level of 12%, reflecting very poor glycemic control. A family medicine approach was applied through detailed history taking, physical and laboratory examinations, home visits, and completion of a family folder to assess clinical, personal, social, and functional aspects. Interventions included counseling on balanced diet, encouragement of regular physical activity, education on diabetic foot care, and pharmacological treatment with metformin and insulin. The family received counseling about hereditary risk factors, the importance of emotional support, and the need for consistent monitoring of health status. The patient was still capable of light daily activities, supported by a highly functional family environment with an APGAR score of 10. A holistic family medicine–based approach was shown to improve treatment adherence, patient knowledge, and overall quality of life. Therefore, management of T2DM requires a comprehensive strategy that integrates promotive, preventive, curative, and rehabilitative components, emphasizing the active involvement of family and community at the primary care level to reduce complications, slow disease progression, and enhance patient well-being.